Improvement of Calcium Aluminate Cement Containing Blast Furnace Slag at 50°C and 315°C - Zhiqiang, Wu; Hengjie, Liu; Xiong, Qu; Guangai, Wu; Xuesong, Xing; Xiaowei, Cheng; Xiucheng, Ni (Frontiers in Materials, 2022)
During the thermal recovery of heavy oil thermal recovery wells, improving the mechanical properties and integrity of the cement ring is of great significance for the safe and efficient exploitation of heavy oil resources. This paper studies the relative properties of calcium aluminate cement and three kinds of slags under the conditions of 50°C × 1.01 MPa and 315°C × 20.7 MPa. CAC-slag composite material performance was evaluated using the cement paste compressive strength and permeability tests to study the physical properties of CAC with blast furnace slag. X-ray diffraction analysis, scanning electron microscopy (SEM), and thermal analysis (DSC/TG) were carried out to investigate the mineralogical composition of CAC with blast furnace slag. Results show that adding blast furnace slag did not affect the performance of cement slurry. Moreover, C2ASH8 curing occurred at low temperature, the microstructure of CAC paste was compact, and the permeability resistance was improved, thus improving the low-temperature properties of neat CAC. When cured at a high temperature, the CAC paste was mainly hydrated with C3ASH4 and AlO(OH), which had a well-developed crystal structure. Adding blast furnace slag can improve the CAC resistance to high temperature.